Enhanced glycolysis in the myometrium with ectopic endometrium of patients with adenomyosis: a preliminary study - Shiya Huang; Xueqian Huang; Xiaohui Wen; Xuehong Liu; Hongxia Ma; Linling Xie; Yishu Wang; Shanjia Liu; Yongge Guan; Kunyin Li (Gynecological Endocrinology, 2024)
Objectives The objective of this study was to investigate the glycolytic activity of adenomyosis, which is characterized by malignant biological behaviors including abnormal cell proliferation, migration, invasion, cell regulation, and epithelial-mesenchymal transition.Methods From January 2021 to August 2022, a total of 15 patients who underwent total hysterectomy for adenomyosis and 14 patients who had non-endometrial diseases, specifically with cervical squamous intraepithelial neoplasia and uterine myoma, were included in this study. Myometrium with ectopic endometrium from patients with adenomyosis while normal myometrium from patients in the control group were collected. All samples were confirmed by a histopathological examination. The samples were analyzed by liquid chromatography-mass spectrometry (LC-MS), real-time quantitative PCR, NAD+/NADH assay kit as well as the glucose and lactate assay kits.Results Endometrial stroma and glands could be observed within the myometrium of patients in the adenomyosis group. We found that the mRNA expressions of HK1, PFKFB3, glyceraldehyde-3-phospate dehydrogenase (GAPDH), PKM2, and PDHA as well as the protein expressions of PFKFB3 were elevated in ectopic endometrial tissues of the adenomyosis group as compared to normal myometrium of the control group. The level of fructose 1,6-diphosphate was increased while NAD + and NAD+/NADH ratio were decreased compared with the control group. Besides, increased glucose consumption and lactate production were observed in myometrium with ectopic endometrium.Conclusions We concluded that altered glycolytic phenotype of the myometrium with ectopic endometrium in women with adenomyosis may contribute the development of adenomyosis.